Analisis Capaian Perkembangan Sosial Anak Usia 4-5 Tahun Berdasarkan Pekerjaan Orangtua di TK Efrata Medan - Vany Adilah Prayoga; Suri Handayani Damanik (Universitas Negeri Medan, 2026)
Based on the results of research with children aged 4-5 years in Efrata Kindergarten Medan, researchers obtained information and facts in the class that there were several students whose social development based on their parents' work was studied. So this study aims to find out how the achievements of social development of children aged 4-5 years based on their parents' work in Efrata Kindergarten Medan. This type of research is qualitative research with the subjects and objects of research, namely children aged 4-5 years in Efrata Kindergarten Medan, totaling 4 students where this study uses descriptive research with the aim of describing the achievements of children's social development based on their parents' work in Efrata Kindergarten Medan. After this research was conducted, the results of this study showed that the social interactions of children aged 4-5 years with peers and adults in Efrata Kindergarten Medan included 2 responses, namely action and communication, The self-confidence of children aged 4-5 years in Efrata Kindergarten Medan showed positive self-confidence such as daring to appear and negative self-confidence such as fear and crying, The responsibility of children aged 4-5 years in Efrata Kindergarten Medan showed that some could be responsible for their duties well and some could not be responsible for their duties well.